Linkages between biological and cultural diversity for participatory management: Nepal’s experiences with Makulu-Barun National park and its buffer zone - Jha, Shree Gopal (Banko Janakari, 2008)
The Makalu-Barun National Park (MBNP) and its Buffer Zone (BZ) of eqastern Nepal shares is borders with Sagarmatha National Park on the west and with the Qomolongma Natural Preserve of the Tibet Autonomous Region of China on the North. The Park is rich in cultural diversity with many ethnic groups. Most of the households are economically poor and depend on subsistence agriculture, animal husbandry and diverse natural resources for livelihoods. Slash and burn cultivation on steep slopes, poaching, hunting, over grazing, high dependency on natural resources, poverty and food deficits are the main threats to biodiversity in MBNP and BZ area. The MBNP was established in 1991 while its BZ was declared in 1998. the basic underlying approach of protection and management of the Park and its BZ is biodiversity conservation through people participation, without relying on military force. This paper highlights the implementation of the biodiversity conservation and management approaches through people participation in the MBNP and its BZ, and also explores notable achievements and effectiveness of partnership of the Government of Nepal, the Mountain Institute (TMI) – an INGO and the local communities to sustain conservation efforts as well as to improve local livelihoods. Key words: Biodiversity; National Park; Buffer Zone; participation; culture; linkages Banko Janakari Vol.16(2) 2006 pp.37-44